Direct evidence of attempted beta cell regeneration in an 89-year-old patient with recent-onset type 1 diabetes - Meier, J. J.; Lin, J. C.; Butler, A. E.; Galasso, R.; Martinez, D. S.; Butler, P. C. (Diabetologia, 2006)
We investigated whether there was evidence of attempted beta cell regeneration in the pancreas obtained from a patient with recent-onset type 1 diabetes, and if so by what mechanism this occurred. We examined pancreas tissue from a lean 89-year-old patient (BMI 18.0 kg/m(2)) with recent-onset type 1 diabetes who had had a distal pancreatectomy to remove a low-grade pancreatic intraepithelial neoplasia. In the tumour-free tissue, the fractional beta cell area was 0.54+/-0.2% of pancreas area (about one-third of that in non-diabetic humans). CD3-positive T lymphocytes and macrophages had infiltrated the majority of the islets. Subclassification of the T cell population revealed a predominance of CD8-positive cells over CD4-positive cells. Beta cell apoptosis (terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick-end labelling [TUNEL] staining) was greatly increased, consistent with ongoing immune-mediated beta cell destruction. There was also a marked increase (more than approximately 100-fold) in the frequency of beta cell replication (0.69+/-0.15% Ki67-positive beta cells) in all blocks examined. The present report provides direct evidence of attempted beta cell regeneration through the mechanism of beta cell replication in a case of newly diagnosed type 1 diabetes, and affirms that beta cell apoptosis is an important mechanism for beta cell loss in type 1 diabetes.